Analisis Mekanisme Transmisi Kebijakan Moneter Melalui Saluran Harga Aset Pada Sektor Riil - Yolanda Argi Utami; Thomas Andrian (Universitas Negeri Padang, 2022)
The purpose of this study is to see how the variable response of the monetary policy transmission mechanism of the asset price channel in the real sector when there is a change in each variable and to see the contribution of the SBK, rPUAB, rKREDIT, IHPR, INV, OG, and INF variables to the final target. monetary policy reflected in inflation. The analytical method used is the Vector Error Correction Model (VECM) with the analysis of Impulse Responses (IR) and Variance Decomposition (VD). The results of the impulse response analysis show that the policy interest rate, interbank interest rate, credit interest rate, IHPR, investment and output gap variables quickly respond to the shock that occurs in each variable at the beginning of the period. The results of the analysis of variance decomposition in model 1 show that apart from the INF variable itself, each variable has a different contribution to the level of INF with the order of the greatest influence being the output gap (OG), IHPR, and INV. For further researchers, it is hoped that they will be able to do further research on the Residential Property Price Index (IHPR), especially the factors that influence it other than credit interest rates.